2019
DOI: 10.29408/jel.v5i1.1022
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Lembar Kerja Siswa Berbasis Etnomatematika Tenun Timor pada Materi Pola Bilangan

Abstract: This research was motivated by the fact that there are no available learning resources in accordance with the conditions and situations of everyday students in the border area. This research aims to (i) design student’s worksheets which are valid and practical; (ii) determine the potential effects or the effectiveness of students worksheet toward student outcomes in learning number pattern. The development research method was used which is consist of preliminary study and formative evaluation. Data is collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 0 publications
4
5
0
7
Order By: Relevance
“…It is seen in Table 2. From the various stages and analysis that has been done, the purpose of this research is said to have been achieved and obtained results in the form of products that have qualified validity and practicality, it in accordance with the opinion (Disnawati & Nahak, 2019).…”
Section: Resultssupporting
confidence: 55%
“…It is seen in Table 2. From the various stages and analysis that has been done, the purpose of this research is said to have been achieved and obtained results in the form of products that have qualified validity and practicality, it in accordance with the opinion (Disnawati & Nahak, 2019).…”
Section: Resultssupporting
confidence: 55%
“…Learning using ethnomathematics-based LKM has brought students to achieve learning completeness, therefore learning using ethnomathematics-based learning can be used to train students' ability to understand mathematical concepts. This is in line with Disnawati & Nahak (2019), the developed worksheets can be indicated from the learning outcomes of students both in writing and orally during the field test. More than 80% of students achieved the completeness criteria and based on questionnaires and interviews it was found that students were very fond and motivated to learn mathematics using ethnomathematicsbased worksheets.…”
Section: Resultssupporting
confidence: 77%
“…Uji coba produk untuk meyakinkan modul pembelajaran yang didasari dengan respon peserta didik berikan. Adapun respon yang diberikan adalah keantusiasan dan sangat tertarik dengan modul pembelajaran matematika berbasis etnomatematika berbantuan Wingeom (Sari et al, 2018;Wijayanto 2017;Disnawati & Nahak 2019 Berdasarkan Tabel 4 di atas menunjukkan bahwa pada uji coba produk memperoleh persentase rata-rata 79,72% dengan kriteria "Sangat Menarik". Uji kemenarikan dilakukan dengan 2 tahap yaitu uji coba produk dengan skala kecil dan uji coba produk dengan skala besar.…”
Section: Gambar 6 Hasil Uji Validasi Oleh Ahli Bahasaunclassified